Representative Studies on Victimisation Research Findings from Germany - Pfeiffer, Christian (Interdisziplin, 2016)
Representative research on crime rates and their trends in Germany is sparse. A major research focus at the Criminology Research Institute in Lower Saxony, which is where all the papers compiled in this volume come from, is on victimisation. In recent years, research here was carried out on risk factors of victimisation, on vicitimsation of different population groups and on the consequences of victimisation. All the papers in this book centre on the presentation of findings from empirical research projects. These include both large-scale standardised surveys and qualitative interview studies with small numbers of interviewees.